Decadal evolution of fluvial islands and its controlling factors along the lower Yangtze River - Wu, Jingtao; Fan, Manman; Zhang, Huan; Shaukat, Muhammad; Best, James L.; Li, Na; Gao, Chao (Frontiers in Environmental Science, 2024)
Fluvial islands are vital from both morphological and ecological perspectives and consequently have been hotspots of morphodynamic research in large rivers around the world. There are many fluvial islands in the lower Yangtze River and the areas of these islands change rapidly. In the present study, 14 representative fluvial islands were studied in the lower reaches of the Yangtze River. Historical aerial images (1945, 1976, 1986, 1996, and 2016) were used to map the island boundaries in the lower reaches of the Yangtze River. The spatial-temporal evolution of the selected fluvial islands, including their shape and area dynamics during 1945–2016, was analyzed by interpreting remote sensing images and analyzing the hydrological data. The results indicated that: (1) the total area of the 14 fluvial islands showed a growing trend at an average rate of 0.30 km2 yr-1 during the 72 years; (2) the island Fenghuangzhou (FHZ) experienced the largest change in area, while Xiaohuangzhou (XHZ) had the smallest change in area; (3) Sediment discharge and flooding were assumed to be the primary natural factors controlling the island dynamics. Furthermore, dam construction and bank reinforcement also played a critical role in preventing shoreline collapse, improving channel conditions, and promoting the stability of fluvial islands; (4) From 1976 to 2016, maximum erosion occurred on the left XHZ, while maximum accretion was found on the Qingjiezhou island (QJZ). Almost the entire river section experienced an accretion process on the right bank, which was assumed to be caused by the construction of erosion control structures. The dynamics of the fluvial islands along the lower Yangtze River appears to follow the erosion processes of the river bank. From the results obtained from analyzing remote sensing images and hydrological data, this study can provide an important reference for sustainable utilization and management of islands.